(untitled) (Bangladesh Journal of Agricultural Research, 2010)
Seedling bed netted with mosquito net barrier against red pumpkin beetle, Aulacophora foveicollis (Lucas) in sweet gourd was evaluated with other chemical, mechanical, and botanical approaches during 2006-07 and 2007-08 cropping seasons. Among six treatments, results indicated that seedling bed of sweet gourd covered with mosquito net barrier upto 45 days before planting was found to be most effective and provided 97.59 and 100% protection with higher benefit cost ratio of 21.99 compared to 9.74 with Furadan 5G applied in soil; as of 4.35 using neem seed oil for the average of two years applied against red pumpkin beetle. Keywords: Mosquito net barrier; cucurbit; pumpkin beetle. DOI: 10.3329/bjar.v35i3.6446 Bangladesh J. Agril. Res. 35(3) : 395-401